THIN WALLED CRYOGENIC MACHINING ON INCONEL OR AEROSPACE MATERIALS - Arie Yudha Budiman; Amrifan Saladin Mohruni (Universitas Sriwijaya, 2020)
Conventional liquids and lubricants are widely used in machining processes throughout the world. However, this cutting liquid is the source of many environmental pollution problems. In order to reduce or eliminate the effect produced by cutting fluids, it is necessary to switch to a continuous machining technique such as using small amounts of cutting fluid, liquid nitrogen, vegetable oil or compressed air as a cooling lubrication medium. Cryogenic coolant is found to be more efficient, economical, cost-effective and environmentally friendly when compared to the conventional coolant, especially in mass production. In machining difficult-to-cut materials such as thin walled materials for the aerospace industry, cooling applications are needed. Ni-based superalloy, Inconel is a material for aerospace applications because of its high durability to wear and material that is resistant to oxidation and corrosion at high temperatures. This paper presents a review and explanation of thin wall machining using cryogenic cooling systems on inconel or aerospace materials.